2003
DOI: 10.1046/j.1365-294x.2003.01879.x
|View full text |Cite
|
Sign up to set email alerts
|

The demographic history of the New Zealand short‐tailed bat Mystacina tuberculata inferred from modified control region sequences

Abstract: Short-tailed bats Mystacina tuberculata were widespread throughout the forest that dominated prehuman New Zealand, but extensive deforestation has restricted them to scattered populations in forest fragments. In a previous study, the species' intraspecific phylogeny was investigated using multiple mitochondrial gene sequences. Six phylogroups were identified with estimated divergences of 0.93-0.68 Ma. In the current study, the phylogeographical structure and demographic history of the phylogroups were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 56 publications
2
42
0
Order By: Relevance
“…However, recently Ho et al (2005) showed that the rate of mitochondrial evolution is elevated and highly variable at these shorter divergence times and so cannot be expected to behave in clock-like manner. Nevertheless, these studies of forest-dependent species imply that little gene flow occurred between the two islands probably because the land bridge was likely to have been 'limited and intermittent' during the Pleistocene (Lloyd 2003a). Also these studies indicate that forested refugia existed in the South Island of New Zealand throughout the Pleistocene and thus allowed the survival of lineages distinct from those on the North Island.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, recently Ho et al (2005) showed that the rate of mitochondrial evolution is elevated and highly variable at these shorter divergence times and so cannot be expected to behave in clock-like manner. Nevertheless, these studies of forest-dependent species imply that little gene flow occurred between the two islands probably because the land bridge was likely to have been 'limited and intermittent' during the Pleistocene (Lloyd 2003a). Also these studies indicate that forested refugia existed in the South Island of New Zealand throughout the Pleistocene and thus allowed the survival of lineages distinct from those on the North Island.…”
Section: Discussionmentioning
confidence: 84%
“…For example, studies by Lloyd (2003aLloyd ( , 2003b found New Zealand's endemic Short-tailed Bat contains six distinct mitochondrial lineages that probably diverged in the mid-Pleistocene owing to allopatric fragmentation. The North Island lineages show evidence of population expansion and the mixing in the central region of the Island but the distribution remains consistent with an isolation-by-distance dispersal model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geographic range and numbers of bats have declined significantly and in many areas declines are continuing (e.g. O'Donnell 2000a;Lloyd 2003aLloyd , 2005Pryde et al 2005Pryde et al , 2006. Declines result from a combination of threats, primarily predation and competition from introduced mammalian pests, habitat degradation, disturbance and, possibly, disease (see below).…”
Section: Discussionmentioning
confidence: 99%
“…The total population was estimated as being in the order of 40,000 individuals in eight populations in 2002 (Table 2; Lloyd 2003a, b). A small population in the Tararua Ranges, previously grouped with southern lesser shorttailed bats, has been re-assigned to this taxon on the basis of recent genetic analyses (Lloyd 2003a). We classified central short-tailed bats as Declining.…”
Section: Central Lesser Short-tailed Batmentioning
confidence: 99%